The Effect of Porphyromonas gingivalis Lipopolysaccharide-Induced Periodontitis in Rats Fed a High-Cholesterol Diet on Macrophage Number - Sari, Finsa Tisna; Tandelilin, Regina Titi Christinawati; Rahman, Friska Ani; Mardhiyah, Iffah; Widita, Elastria (Journal of Indonesian Dental Association, 2021)
Introduction: Periodontitis is a chronic inflammatory condition of the tooth-supporting tissue. P. gingivalis, which produces virulence factors, including lipopolysaccharide (LPS), is the main pathogenic driver of periodontitis. However, the interaction between the innate immune system and periodontal pathogens in hyperlipidemia remains unclear. Objective: The aim of this study was to investigate the effect of a high-cholesterol diet (HCD) on macrophage activity in P. gingivalis LPS-induced periodontitis. Methods: Twenty-eight male Sprague Dawley rats were divided into four groups (n=7 rats each group): LPS-HCD, saline-HCD, LPS-basal diet (LPS-BD), and saline-BD. HCD group had been being feeding by high cholesterol diet (1% cholesterol (w/w) and 0.5% cholic acid (w/w)) for 30 days before were injected with 0.2 ml of P. gingivalis ATCC 3277 LPS (LPS-HCD group) and saline (saline-HCD group). The other two groups had been being feeding by normal basal diet for 30 days before were injected with 0.2 ml of P. gingivalis ATCC 3277 LPS (LPS-BD group) and saline (saline-BD group). Rats were sacrificed and lower jaws were harvested and embedded in paraffin. Paraffin section of lower right and left incisor were deparaffinized, rehydrated, and stained with hematoxylin & eosin (H&E). The total number of macrophages was counted using a light microscope at a magnification of 400× from 10 fields of view. Results: The number of macrophages in the LPS-HCD group was the highest compare to LPS- BD, saline-HCD, and saline-BD groups. In addition, LPS-BD group had higher number of macrophage than saline-BD group which had the lowest number of macrophages. Conclusion: HCD and P. gingivalis LPS-induced periodontitis can contribute to increasing of macrophage activity in periodontitis. Thus, HCD itself can enhance the process of inflammation in periodontitis.